Persistence with and adherence to fingolimod compared with other disease-modifying therapies for the treatment of multiple sclerosis: a retrospective US claims database analysis. (October 2014) - Bergvall, Niklas; Petrilla, Allison A.; Karkare, Swapna U.; Lahoz, Raquel; Agashivala, Neetu; Pradhan, Ashish; Capkun, Gorana; Makin, Charles; McGuiness, Catherine Balderston; Korn, Jonathan R.
Abstract Objective: Achieving therapeutic goals in multiple sclerosis (MS) requires strict adherence to treatment schedules. This retrospective study analyzed persistence with, and adherence to, fingolimod compared with injectable/infusible disease-modifying therapies (DMTs) in patients with MS. Methods: Patients in the PharMetrics Plus™ US administrative claims database with at least one prescription for, or administration of, fingolimod, glatiramer acetate (GA), interferon (IFN), or natalizumab (index DMT) between October 1, 2010 and September 30, 2011 were included. Patients were naïve to index DMT (no claim in the previous 360 days) and had an MS diagnosis code within 360 days of the first index DMT prescription. Outcomes were persistence, risk of discontinuing index DMT (evaluated by a Cox proportional hazards model), adherence (measured using the medication possession ratio [MPR] and proportion of days covered [PDC] in patients with at least two index DMT prescriptions), and the risk of being non-adherent (MPR <80% and PDC <80%, assessed using a logistic regression model). Results: The study included 3750 patients (fingolimod, n = 889; GA, n = 1233; any IFN, n = 1341; natalizumab, n = 287). Discontinuation rates (fingolimod, 27.9%; GA, 39.5%; IFN, 43.7%; natalizumab, 39.5%; all p < 0.001) and risk of discontinuation were significantly higher (hazard ratios vs fingolimod [95% confidence interval]: GA, 1.75 [1.49–2.07]; IFN, 2.01 [1.71–2.37]; natalizumab, 1.53 [1.22–1.91]) for patients receiving other DMTs compared with fingolimod. The risk of being non-adherent was also lower for patients in the fingolimod cohort than the other treatment cohorts, irrespective of whether non-adherence was defined as MPR <80% (p < 0.05 for all) or PDC <80% (p < 0.05 for GA and IFN). Limitations: As with all studies assessing real-world treatment patterns it is unclear if medications were used as prescribed. Conclusions: In a real-world setting, persistence with, and adherence to, oral fingolimod was higher than for injectable and infusible DMTs.